REFORMASI PEMIKIRAN MUHAMMAD RASYID RIDHA DALAM HUKUM KELUARGA ISLAM KONTEMPORER - Endah Mustika Pertiwi (El-Ahli : Jurnal Hukum Keluarga Islam, 2024)
This research aims to analyze Muhammad Rasyid Ridha's thoughts on the condition of Muslims in the contemporary realm. As a reform scholar in Islamic thought, Rasyid Ridha contributed many of his thoughts in the realm of education, social and law with the characteristic of revisiting Islamic laws based on the Qur'an and Hadith which were then revitalized in accordance with the conditions of the people. This research investigates Rasyid Ridha's thoughts on family law reform because many of Rasyid Ridha's thoughts were influenced by the social conditions at that time, especially women's rights in family law. This study found that Rasyid Ridha in contemporary thought; the decision to polygamy must be based on something logical and urgent, allowing interfaith marriages on the condition of similarity of values and principles between partners, the right to divorce for women and the calculation of inheritance in accordance with the amount of responsibility of their role in the family. This research uses the literature analysis method, deeply examining data sources in the form of documents and texts that are relevant to the issues raised.